"Tales from the grave": what can we learn from failed international companies?. Issue 5 (14th September 2015) - Amankwah-Amoah, Joseph; Zhang, Hongxu
Abstract : Purpose: – The purpose of this paper is to examine how organisational closure can inform strategic foresight. Design/methodology/approach: – The authors draw insights from illustrative cases, i.e. Swissair, Sabena and Cameroon Airlines to illustrate their theoretical analysis. Findings: – The study shed light on the effects of internal and external factors in precipitating business closures. The authors established that top executives' hubris, resistance to change and over-reliance on external consultants are some of precursors to organisational closure. Research limitations/implications: – The analysis of this paper provides a range of strategies that organisations can pursue to learn from other firms' closure and improve their survivability and chances of future success. Originality/value: – Despite a growing body of literature on strategic foresight and organisational closure, the literature has largely developed in isolation and as such the understanding of the relationship between strategic foresight and organisational closure has remained severely limited. The paper integrates these two streams of research to enrich the understanding of how firms can learn from others to improve their strategic foresight.